Growing Interest in Global Health Among Trainees: The Need for Increasing Training Opportunities for Residents and Fellows in Oncology - Darya Kizub; Chidinma P. Anakwenze; Han Cun; Kathleen M. Schmeler; Cameron E. Gaskill (Global Health, Epidemiology and Genomics)
Conclusions: We found significant interest in global health among trainees in oncology specialties at MD Anderson. As a result, the institution is implementing the Global Cancer Care Track for all trainees. The track includes a formalized curriculum, mentorship, research, and clinical opportunities to develop future leaders in global oncology with the goal of improving cancer care in low-resource settings.